EFFECT OF PRE- Î³-IRRADIATION DOSE ON THE DURABILITY OF THE SULFONATED ETFE-G-POLYSTYRENE CONDUCTING MEMBRANES - Upita Septiani; Hitoshi Kubota (Jurnal Riset Kimia, 2012)
The influence of pre-g-irradiation dose on durability of the poly(ethylene-co-tetrafluoroethylene) (ETFE) film-based radiation-grafted polymer electrolyte membrane was investigated. The durability of membrane was found to be strongly influence by g-ray pre-irradiation dose. The durability was tested in a 3% H2O2 aqueous solution at 60Â°C. The durability of the polymer electrolyte membrane with a degree of grafting of about 30% prepared by lower pre-irradiation dose was more stable than that of the membrane prepared with higher pre-irradiation dose.